Kualitas Ekstrak Etanol 70% Daun Kelor (Moringa oleifera Lamk) dalam Ramuan Penambah ASI - Alegantina, Sukmayati; Isnawati, Ani; Widowati, Lucie (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2013)
From the collection of data (SDKI) in 2002-2003, it is found that the number of exclusive breastfeeding in infants below the age of two months covers only 64% of total infants. The most alarming facts are that 13% of infants under two months have been fed infant milk formula and one of three infants aged 2-3 months has been given additional food. Therefore, using Kelor as herba to facilitating breast milk is needed as extract requirement. In addition, this research considers characterization of Kelor extract as a first step to standardize Kelor extract. Sample is extract of Kelor leaf from East Java. To ensure quality requirements of 70% ethanol extract from Kelor leaf for herbal medicine, it has to meet the quality requirement guidelines established by BPOM. Examination includes non-specific parameter such as water content, total ash, total acid insoluble ash, and extract microscopic examination. In the other side, specific parameter includes content of dilute alkohol, content of dilute water, assay of total alkaloid and chemistry compound test. Characteristic of 70 % ethanol extract from Kelor leaf for non-specific parameter are water content 15,68%, total ash 3,04%, total acid insoluble ash 1,13% and loss on drying 29,70% , whereas characteristic of spesific parameter for content of dilute etanol 33,11%, content of dilute water 47,53%, and assay Trigonellin 15,68 %. The conclusion is non spesific characteristic from kelor leaf etanol extract, that is water content does not meet the quality requirement guidelines